A Decision-Support System application in retail store location model: a case study of hypermarket in emerging markets. (5th April 2011) - Hemalatha, M.; Sridevi, P.; Sivakumar, V.J.
The primary objective of this paper is to develop a suitable DSS framework to evaluate the critical factors that influences the selections of retail store location by reducing uncertainty in location decisions. Store location is a significant factor which decides the success or failure of a retail business. In planning a new retail store location, the impact of location factors like labour cost, rent, availability of skilled labour, population, economic base, legal base and competition are essential. Based on this, a framework using multi criteria decision model was developed to provide a way for the retailers to have a more comprehensive approach to the retail location decision.